2015
DOI: 10.4103/0301-4738.162577
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal thickness profile in healthy Indian children

Abstract: Purpose:The purpose was to study choroidal thickness and its profile based on location in healthy Indian children using enhanced depth spectral-domain-optical coherence tomography (SD-OCT).Methods:In this cross-sectional observational study 255 eyes of 136 children with no retinal or choroidal disease were consecutively scanned using enhanced depth SD-OCT. Eyes with any ocular disease or axial length (AXL) >25 mm or < 20 mm were excluded. A single observer measured choroidal thickness from the posterior edge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
36
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 27 publications
5
36
2
Order By: Relevance
“…To the best of our knowledge, we are the first to demonstrate that the recovery of amblyopia had no significant effect on choroidal thickness. In our study, as in previous studies, choroidal thickness was significantly correlated with axial length. Therefore, it can be stated that the thickening of the choroid that has been found previously in the eyes with hyperopic anisometropic amblyopia may be an artefact of the correlation between choroidal thickness and hyperopia.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…To the best of our knowledge, we are the first to demonstrate that the recovery of amblyopia had no significant effect on choroidal thickness. In our study, as in previous studies, choroidal thickness was significantly correlated with axial length. Therefore, it can be stated that the thickening of the choroid that has been found previously in the eyes with hyperopic anisometropic amblyopia may be an artefact of the correlation between choroidal thickness and hyperopia.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, Mori and colleagues speculated that choroidal accommodation might be inhibited with the diminutive visual feedback in the amblyopic eye; however, in all of these studies, amblyopic eyes were more hyperopic than the control eyes and it was not clear whether this choroidal thickening resulted from amblyopia or hyperopia. It has been demonstrated that there is a positive correlation between SE and choroidal thickness and a negative correlation between axial length and choroidal thickness . To the best of our knowledge, we are the first to demonstrate that the recovery of amblyopia had no significant effect on choroidal thickness.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Ruiz-Moreno et al 29 reported that the temporal choroid was thicker than the subfoveal choroid in the pediatric population. On the other hand, Chhablani et al 30 reported that subfoveal choroid was thicker than temporal choroid. Consistent with their study, in our study the subfoveal choroid was thicker than the temporal choroid.…”
Section: Discussionmentioning
confidence: 98%
“…A wide variation in choroidal thickness was reported in various studies. Even in comparision with Indian studies 15,17 our measurement of choroidal thickness is significantly higher. This could be due to differences in Choroidal thickness in the inferior quadrant is lesser at all corresponding points compared to superior quadrant The average choroidal thickness in the superior quadrant observed in this study is 350.91 μm, which was not significantly different from the choroidal thickness in the subfoveal region.…”
Section: Discussionmentioning
confidence: 75%